Implementasi Model Two Stay Two Stray Terintegrasi Padlet untuk Peningkatan Hasil Belajar Sejarah Peserta Didik Kelas XI 1 SMA Negeri 8 Surakarta Tahun Ajaran 2024/2025 - Natalia Priskilla Putri; Sri Wulandari; Sarikit Nuringhati; Sutiyah Sutiyah (Universitas Sebelas Maret, 2025)
This classroom action research aimed to improve history learning outcomes and student engagement in Grade X1 at SMAN 8 Surakarta, focusing on the physical struggle for Indonesian independence. Initial observations indicated low learning outcomes and passive student participation. The research implemented the Two Stay Two Stray (TSTS) cooperative learning model integrated with the Padlet digital collaboration platform. The study followed Kemmis & McTaggart’s action research model, conducted over two cycles with 35 students during the 2024/2025 academic year. Data were collected through pre-tests, post-tests, observation sheets for student activities and teacher performance, student response questionnaires, and documentation. Results showed a significant improvement in learning outcomes, with the class average score increasing from 62.3 (pre-cycle) to 75.8 (Cycle I) and further to 85.1 (Cycle II). Classical completeness rose from 34.3% (pre-cycle) to 65.7% (Cycle I) and reached 91.4% (Cycle II). Student activity and collaboration also markedly improved, with active participation increasing from 55% in Cycle I to 88% in Cycle II. Student responses indicated high interest and positive perceptions towards the TSTS-Padlet integrated model. The findings underscore the effectiveness of integrating the TSTS model with Padlet in creating a more interactive, collaborative, and engaging learning environment, thereby enhancing history learning outcomes